2010
DOI: 10.1080/1745039x.2010.520407
|View full text |Cite
|
Sign up to set email alerts
|

Effects of folic acid supplementation to rations differing in the concentrate to roughage ratio on ruminal fermentation, nutrient flow at the duodenum, and on serum and milk variables of dairy cows

Abstract: The present study was undertaken to determine the effects of dietary folic acid (FOL) supplementation on ruminal fermentation, duodenal nutrient flow, serum and milk variables, and on B-vitamin concentration in serum. The study was divided into two experiments: in Exp. 1 the forage to concentrate (F:C) ratio of the diet (DM basis) was 34:66 (high concentrate, HC), while in Exp. 2 the F:C ratio was 66:34 (high forage, HF). In addition, the cows received 0 or 1 g FOL/d. In Exp. 1, two German Holstein cows equipp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 31 publications
1
12
0
Order By: Relevance
“…The increased ruminal NDF degradability of corn silage with PRFA supplementation was consistent with the previous study in which the fibre degradability increased by 42% with folic acid supplementation at 100 g in 20 mL medium (Hall et al, 1953). Similarly, Ragaller et al (2010) found that the addition of folic acid at 1 g/d improved the degradability of ADF based on the high forage diet. The positive results of supplementary folic acid on in situ ruminal degradability can be confirmed by the improved milk production and milk protein percentage with increasing RPFA supplementation (0, 1 or 2 g/day) from 3 weeks prepartum to 15 weeks postpartum (Li et al, 2016).…”
Section: Ruminal Degradabilitysupporting
confidence: 90%
See 2 more Smart Citations
“…The increased ruminal NDF degradability of corn silage with PRFA supplementation was consistent with the previous study in which the fibre degradability increased by 42% with folic acid supplementation at 100 g in 20 mL medium (Hall et al, 1953). Similarly, Ragaller et al (2010) found that the addition of folic acid at 1 g/d improved the degradability of ADF based on the high forage diet. The positive results of supplementary folic acid on in situ ruminal degradability can be confirmed by the improved milk production and milk protein percentage with increasing RPFA supplementation (0, 1 or 2 g/day) from 3 weeks prepartum to 15 weeks postpartum (Li et al, 2016).…”
Section: Ruminal Degradabilitysupporting
confidence: 90%
“…Nevertheless, Girard et al (1994) found that the quantity of protein per unit of microbial mass was not modified by the dietary supplement of folic acid. Ragaller et al (2010) also found microbial protein flow to the duodenum reduced when the cows fed the high concentrate diet (forage to concentrate ratio: 34:66) and received folic acid at 0 or 1 g/d, because the ruminally fermented organic matter decreased with folic acid supplementation and then less energy was available for ruminal microorganisms. As discussed previously, these inconsistent results could be associated with the different administration practices and quantity of folic acid given as well as dietary composition.…”
Section: Purine Derivatives Excretionmentioning
confidence: 88%
See 1 more Smart Citation
“…Wang et al (2016) found similar results with RPFA supplementation in steers. Other studies also reported that fibre degradability was increased by 42% with FA supplementation in vitro (Hall et al 1953), and in situ ruminal ADF degradability was improved by supplementary FA (Ragaller et al 2010). Similarly, improved digestibilities of NDF, ADF and CP with increasing dietary CP levels were observed in cows (Weigel et al 1997; Broderick 2003).…”
Section: Discussionmentioning
confidence: 94%
“…2017), and FA addition increased total tract digestibility in calves (Wang et al, 2019). Ragaller et al (2010) also found that ruminal ADF degradability increased with FA addition in a high-forage diet of dairy cows.…”
Section: Growth Performance and Total Tract Digestibility Coefficientmentioning
confidence: 72%